2015
DOI: 10.1111/apm.12469
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant metastatic behavior and particular features of early gastric cancer

Abstract: In this paper, we have focused on the metastatic behavior of EGC and its particularities. The main factors that are currently considered as predictors of the metastatic behavior and that are used in the therapeutic decision (endoscopic resection vs surgical removal) are the tumor size (upper or bellow 2 cm), depth of infiltration, angiolymphatic invasion, the presence or absence of ulceration, and histologic type (undifferentiated vs differentiated carcinomas). However, most of the metastatic cases were publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…[ 59 , 60 ] Sentinel node mapping are recommended in patients with EGC who underwent surgical excision to detect possible skip metastasis. [ 61 , 62 ] A single-skip metastasis located along the middle colic artery was unexpectedly detected in sentinel lymph node biopsy of EGC by Bara's group. [ 60 ] Recently, a research showed that LN status (no enlargement of lymph nodes vs swollen lymph nodes) assessed by CT was an independent risk factor for solitary metastatic lymph node, but the specific accuracy in predicting the presence of solitary metastatic lymph node was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 , 60 ] Sentinel node mapping are recommended in patients with EGC who underwent surgical excision to detect possible skip metastasis. [ 61 , 62 ] A single-skip metastasis located along the middle colic artery was unexpectedly detected in sentinel lymph node biopsy of EGC by Bara's group. [ 60 ] Recently, a research showed that LN status (no enlargement of lymph nodes vs swollen lymph nodes) assessed by CT was an independent risk factor for solitary metastatic lymph node, but the specific accuracy in predicting the presence of solitary metastatic lymph node was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the already known factors such as tumor size, histological characteristics, depth of tumor invasion, and lymphovascular invasion, it was observed that the ethnicities of patients and/or their geographic differences influenced lymph node metastasis and aberrant metastatic behavior of early gastric cancer. [ 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Only 79 cases of EGC with bone metastasis had been published. The time interval between the diagnosis of EGC and bone metastasis was reported in 47 cases out of 79 cases, and 17 cases (36.2%) involved synchronous bone metastasis (12). Our case of early gastric cancer with synchronous bone metastasis found taking the back pain as an opportunity, was considerably rare.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, Park et al, reported that the rate of bone metastasis varied depending on the progression of gastric cancer (5). Gurzu et al (12) reviewed the literature on metastasis with early gastric cancer in PubMed from 1983 to 2015. Only 79 cases of EGC with bone metastasis had been published.…”
Section: Discussionmentioning
confidence: 99%